Problematic Analysis of the Legal Policy of the Food Estate Program (Government Era 2020-2024) - Rasji; Vera Tua Tobing (Dinasti Research, 2024)
Food estate development is a response to President Joko Widodo's 2020 warning of a crisis during the pandemic period to meet domestic food needs. The Ministry of Environment and Forestry issued Minister of Environment and Forestry Regulation No.24/2020 concerning the Provision of Forest Areas for Food Estate Development through the Ministry of Environment and Forestry, this regulation was later revoked and replaced by Permen LHK No.7 of 2021. The findings indicate that the food estate development policy conflicts with the principles of ecological justice, which advocate for harmonious coexistence between humans and nature. The food estate concept itself refers to the integrated development of food production, encompassing agriculture, plantations, and livestock over vast tracts of land. The perspective of the ecological justice theory approach suggests that forests need to be preserved not only because humans still need forests to meet their needs, but it is appropriate because humans are actually only one of the elements of the earth's large and complex ecosystem, and as humans who have morals need to respect the rights of non-human beings to coexist in harmony. Therefore, the existing set of regulations must consider the rights of other natural creatures including animals, forests, seas, mountains and other elements of the biospher.